POTENSI BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH PADA MATERI TRIGONOMETRI - Halimatussa'diah Halimatussa'diah; Sugiatno Sugiatno; Romal Ijuddin (Jurnal AlphaEuclidEdu, 2020)
Mathematics learning has an essential role in forming and developing students' critical thinking skills. It is in line with the objectives of learning mathematics, which shows a logical, critical, analytical, careful, and thorough, responsible, responsive, and not easily give up in solving problems. Mathematics taught to students has the aim to equip students to have critical abilities. But in reality, the implementation of mathematics learning in schools has not been able to train students' critical thinking skills. This study aims to describe and find out the potential of students' critical thinking in solving problems in trigonometry in high school. The research method used in this research is descriptive with exploratory research. The subjects in this study were 30 subjects. Based on the results of this study, it was found that the potential for students' critical thinking in solving trigonometry problems was medium. Potential students' critical thinking is categorized as being because students have not been able to understand the problem displayed correctly, students have difficulty in giving arguments or reasons for the answers they have stated, students cannot identify and choose relevant information because of the available mathematical models, students have difficulty in giving questions to the information displayed.Keyword: Critical Thinking, Potential, Trigonometry